Lessons for Research Policy and Practice: The Case of Co-enquiry Research With Rural Communities - Caruso, Emily; Schunko, Christoph; Corbera, Esteve; Isabel Ruiz Mallén; Vogl, Christian R; Martin, Gary; Arrázola, Susana; Fábio Pedro Bandeira; Diana Calvo Boyero; Claudia Camacho Benavides; Thiago Mota Cardoso; Chan-Dzul, Albert; et al. (Journal of research practice, 2016)
This article explores the relationship between institutional funding for research and community-based or co-enquiry research practice. It examines the implementation of co-enquiry research in the COMBIOSERVE project, which was funded by the European Commission’s Seventh Framework Programme for research and innovation, between the years 2012 and 2015. Research partnerships between Latin American and European civil society organisations, research institutions, and Latin American rural communities are analysed. Challenges for effective collaboration in co-enquiry and lessons learned for research policy and practice are outlined. Based on our case study we suggest that: (1) the established values and practices of academia seem largely unfavourable towards alternative forms of research, such as co-enquiry; (2) the policies and administrative practices of this European Commission funding are unsuitable for adopting participatory forms of enquiry; and (3) the approach to research funding supports short engagements with communities whereas long-term collaborations are more desirable. Based on our case study, we propose more flexible funding models that support face-to-face meetings between researchers and communities from the time of proposal drafting, adaptation of research processes to local dynamics, adaptation of administrative processes to the capacities of all participants, and potential for long-term collaborations. Large-scale funding bodies such as European Commission research programmes are leaders in the evolution of research policy and practice. They have the power and the opportunity to publicly acknowledge the value of partnerships with civil society organisations and communities, actively support co-enquiry, and foment interest in innovative forms of research.